Specific theories of crime? A longitudinal assessment of the competing effects of psychopathy and self-control - Altikriti, Sultan (Journal of crime and justice, 2020)
The association between psychopathic personality traits (PPTs) and offending behavior has been studied extensively. Self-control also enjoys strong empirical support in its association with antisocial behavior. Further, research has shown that those with higher PPTs and those with lower self-control are more likely to be antisocial and are more likely to have protracted criminal careers. The current study used latent class growth analysis to compare how PPTs and self-control predict membership in longitudinal offending trajectories among an all-male sample of adjudicated delinquents (n = 726) from the Pathways to Desistance data. The results indicated that PPTs predicted membership across the persistent offending and desisting groups more often than self-control. Self-control, however, more often predicted membership within the persistent offending groups. Although both factors were among the most salient predictors of group membership, the results illustrated specific differences in how each factor can influence longitudinal patterns of offending.